2020
DOI: 10.1186/s13058-020-01376-6
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin V suppresses GATA3 protein expression in luminal A breast cancer

Abstract: Background Lysosomal cysteine protease cathepsin V has previously been shown to exhibit elevated expression in breast cancer tissue and be associated with distant metastasis. Research has also identified that cathepsin V expression is elevated in tumour tissues from numerous other malignancies, but despite this, there has been limited examination of the function of this protease in cancer. Here we investigate the role of cathepsin V in breast cancer in order to delineate the molecular mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
(65 reference statements)
1
24
0
Order By: Relevance
“…Additionally, the overexpression of GATA3 in BT-549 and MDA-MB-231 cells significantly reduced cell migration in vitro and impaired mesenchymal phenotypes, while the opposite results were found following GATA3 knockdown. Our in vitro findings are consistent with the previous reports that GATA3 negatively regulates TNBC progression [20,34,35]. To further clarify how GATA3 diminishes TNBC aggressiveness, we demonstrated here that MFNG is a direct target of GATA3 and that loss of MFNG is associated with less invasiveness and TNBC development in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the overexpression of GATA3 in BT-549 and MDA-MB-231 cells significantly reduced cell migration in vitro and impaired mesenchymal phenotypes, while the opposite results were found following GATA3 knockdown. Our in vitro findings are consistent with the previous reports that GATA3 negatively regulates TNBC progression [20,34,35]. To further clarify how GATA3 diminishes TNBC aggressiveness, we demonstrated here that MFNG is a direct target of GATA3 and that loss of MFNG is associated with less invasiveness and TNBC development in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…In breast invasive ductal carcinoma (IDC) patients, analysis of tissue specimens by IHC revealed that CTSL is expressed in advanced tumor stage patients, CTSB is found in ERα+ tissues with poor disease-free survival (DFS) rates, CTSK is expressed in ERα+/PR+ tumors and, finally, CTSD expression associates with poor prognosis, high incidence of metastasis, especially to the chest, and low DFS rates [ 181 ]. Likewise, CTSV expression favors distant metastasis, hence low survival rates in ERα+ breast cancer, as it facilitates cell proliferation and invasion while attenuating the expression of GATA3 through PI3K-AKT-GSK3β pathway [ 170 ] ( Figure 2 ). In addition, in MCF-7 breast cancer cells CTSB is upregulated while it suppresses E-cadherin.…”
Section: Cathepsins In Tumor Progressionmentioning
confidence: 99%
“…Among the four key PRGs obtained, cathepsin V (CTSV) promotes the proliferation and invasion of tumour cells in breast cancer [13] and colorectal cancer [14], but its role in liver cancer is unclear. CXCL8/IL-8 is a well-known chemokine that mediates cancer cell motility, invasion and metastasis by promoting epithelial-mesenchymal transition (EMT) [15], and IL-8 has been found to increase cancer proliferation in vitro [16].…”
Section: Discussionmentioning
confidence: 99%